DETERMINAN DAN KONSEKUENSI KONSERVATISME AKUNTANSI: MEKANISME CORPORATE GOVERNANCE DAN MANAJEMEN LABA - Ongki, Stephanie; Pangestu, Stevanus (Balance : Jurnal Akuntansi, Auditing dan Keuangan, 2018)
This paper attempts to investigate the effects of (i) corporate governance on accounting conservatism, and (ii) accounting conservatism on earnings management. The internal corporate governance mechanisms included were managerial ownership, institutional ownership, audit committee size, and number of independent commissioners. 119 publicly-traded manufacturing corporations were observed for a time period of 5 years (2012-2016, n=595). The data were analyzed using panel regression. This study finds that the number of commissioners negatively affects accounting conservatism, and that accounting conservatism negatively affects earnings management. It is found that the more conservative a firm reports its finances, the less likely the management would manage its earnings. Whereas other variables were found to be insignificant regressors of accounting conservatism.Â Keywords: Accounting conservatism, earnings management, corporate governance, ownership, manufacturing sector